Istilah Baru Era Pandemi COVID-19 di Bahasa Indonesia dan Bahasa Korea: Kajian Neologisme Pendekatan Linguistik Korpus - Sri Wahyuningsih (Universitas Gadjah Mada, 2022)
This study tries to identify the use of new word (neologisms) during the COVID-19 pandemic era in Indonesian and Korean online newspapers with a corpus linguistic approach. The corpus data collected from online newspaper articles with the theme of COVID-19, both in Korean and Indonesian online newspapers. A total of 2,515,019 words scale of corpus data were used in the study collected from September 1, 2020 to March 31, 2021. Based on the analysis, it was found that in both Indonesian and Korean, neologisms related to the COVID-19 pandemic can be categorized into 4 categories, namely 1) health registers, 2) government policy registers, 3) people's habits, and 4) other categories. The health register occupies the first position with the highest frequency of neologisms both in the Indonesian language, by placing words that refer to COVID-19, namely Covid-19 (Indonesian) and 코로나 19 (khorona ilgu / Korean language) as the most used neologisms. Meanwhile, there are differences in the use of neologisms in the categories of government policies, people's habits, and others. The differences are correlated with the differences in government policies in handling the COVID-19 pandemic and the conditions of the society of both countries.